Intraday return, volatility and optimal time to invest in Malaysia stock market - Lai, Poh Poh (2020)
This study examining whether two distinct U-shape patterns exist in Malaysia stock market and what is the optimal time to invest in Malaysia market, study period from 2 January 2020 to 30 June 2020. The average return for KLSE Composite Index formed a U-shape pattern in the morning session and inverted U in the afternoon session. However, these shape does not exist in the individual stocks. While study the intraday volatility, it is observed there are two distinct U-shape patterns appeared in the Malaysia stock market but regression not able to reinforce the presence of the pattern. Similarly, volatility for individual stocks shown a L shape pattern. Lastly, optimal time to invest in the stock is constructed. The optimal time suggested can help the investor in making their investment decision